Socjolekt rzeszowskich studentów – tradycja międzypokoleniowa czy efemeryczna ekspresywność? - Taras, Bożena (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
Rzeszów, the capital of Podkarpackie Voivodeship, is an academic center with a sixty-seven-year old tradition. Almost sixty thousand students are currently studying here. This group is so numerous that it can be perceived as a social and cultural community with its characteristic language behaviors. The article compares the results of the research on vocabulary concerning educational institutions and studies carried out among the students of Rzeszów universities in 2011–2016 with the lexical resource of students registered in the 1980s. It was observed that Rzeszów students use the vocabulary common to several social varieties of contemporary Polish. However, juxtaposing the sociolectic lexicon, it was noticed that the forms passed down from generation to generation are enriched by ephemeral expressivisms.